Influence of Fourier spatial filtering on multimode fiber bandwidth - Stępniak, Grzegorz; Maksymiuk, Łukasz; Siuzdak, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The paper investigates the influence of the amplitude spatial filtering of the launched light beam on the baseband width of multimode (MM) fiber frequency response. The filter is located on the confocal plane of an 4f imager. The theory presented is verified by an experiment. It is shown that an increase of 3 dB baseband frequency of MM fiber is possible but at the expense of filtration losses.
Optica Applicata, Vol. 40, 2010, nr 4, s. 791-800
Keywords: optyka; data transmission; multimode fiber; spatial filtering; bandwidth